Syntheses and analytical characterizations of N‐alkyl‐arylcyclohexylamines. Issue 8 (11th September 2015) - Wallach, Jason; Colestock, Tristan; Cicali, Brian; Elliott, Simon P.; Kavanagh, Pierce V.; Adejare, Adeboye; Dempster, Nicola M.; Brandt, Simon D.
Abstract : The rise in new psychoactive substances that are available as 'research chemicals' (RCs) remains a significant forensic and legislative challenge. A number of arylcyclohexylamines have attracted attention as RCs and continue to be encountered, including 3‐MeO‐PCP, 3‐MeO‐PCE and 3‐MeO‐PCPr. These compounds are commonly perceived as ketamine‐like dissociative substances and are believed to act predominantly via antagonism of the N ‐methyl‐D‐aspartate (NMDA) receptor. To aid in the identification of newly emerging substances of abuse, the current studies were performed. The syntheses of fifteen N ‐alkyl‐arylcyclohexylamines are described. Analytical characterizations were performed via gas chromatography and high performance liquid chromatography coupled to multiple forms of mass spectrometry as well as nuclear magnetic resonance spectroscopy, ultraviolet diode array detection and infrared spectroscopy. The series consisted of the N ‐alkyl derivatives ( N ‐methyl, N ‐ethyl, N ‐propyl) of phenyl‐substituted and isomeric 2‐, 3‐ and 4‐methoxy phenylcyclohexylamines, as well as the N ‐alkyl derivatives obtained from 3‐methylphenyl and 2‐thienyl moieties. In addition to the presentation of a range of previously unreported data, it was also found that positional isomers of aryl methoxyl‐substituted arylcyclohexylamines were readily distinguishable under a variety of analytical conditions. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A number of N ‐alkyl‐arylcyclohexylamines continue to be explored as 'research chemicals' and continue to be used for non‐medical use. Syntheses and extensive analytical characterizations of fifteen N ‐alkyl‐arylcyclohexylamines are described to aid the identification of newly emerging substances. In addition to the presentation of previously unreported data, three sets of three positional isomers have been included to illustrate the feasibility of distinguishing these isomers.